Epstein-Barr virus-associated hemophagocytic lymphohistiocytosis: response to HLH-04 treatment protocol - Elva Jiménez-Hernández; Octavio Martínez-Villegas; Berenice Sánchez-Jara; María Angélica Martínez-Martell; Beatriz Hernández-Sánchez; Paloma del Rocío Loza-Santiaguillo; Eduardo Pedro-Matías; José Arellano-Galindo (Permanyer, 2016)
Introduction: Hemophagocytic syndrome, macrophage activation syndrome, reactive histiocytosis or hemophagocytic lymphohistiocytosis (HLH) represent a group of diseases whose common thread is reactive or neoplastic mononuclear phagocytic system cells and dendritic cell proliferation. Clinical case: We present a case of an HLH probably associated with Epstein-Barr virus (EBV) in a 4-year-old male patient treated with HLH-04 protocol. Viral etiology in HLH is well accepted. In this case, clinical picture of HLH was assumed secondary to EBV infection because IgM serology at the time of clinical presentation was the only positive factor in the viral panel. Conclusions: Diagnosis of HLH is the critical first step to successful treatment. The earlier it is identified, the less the tissue damage and reduced risk of multiple organ failure, which favors treatment response.